Chinese Professional Consumers at 30: The Rise and Impending Fall - Yi Lu; Herwig C.H. Hofmann; Felix Pflücke (European Journal of Risk Regulation)
This paper introduces a unique phenomenon with a distinctive Chinese regulatory approach. Since 1994, the Consumer Rights Protection Law has afforded consumers the right to seek punitive damages in instances of fraudulent practices. This has given rise to a special profession with Chinese characteristics: professional consumers. Their status as enigmatic figures is a consequence of the fluctuating stance of public authorities. Thirty years of consistent inconsistency has been a rarity in China’s legislative history. The year 2024 marks the 30th anniversary of the enactment of the CRPL, China’s Consumer Rights Protection Law and the birth of its implementing regulation. It is an opportune moment to reassess the regulatory system that enabled this group and reconstruct it for the future. This paper presents a comprehensive regulatory review of the emergence, growth, and projected decline of professional consumers. It examines the reasons for this long-standing regulatory inconsistency through a detailed investigation of China’s legal system. It concludes by projecting two upcoming legal positions. The first is the transformation under the state’s co-governance strategy. The second is the displacement by procuratorial public interest litigation. Although seemingly contradictory, these two positions exemplify a distinctive Chinese approach to the co-governance strategy, which is characterized by the preponderance of public authority.